Cellular stressors contribute to the expansion of hematopoietic clones of varying leukemic potential - Terrence N. Wong (Nature Portfolio, 2018)
Cellular stressors can impact clonal hematopoiesis. Here, the authors explore the impact of cytotoxic therapy and hematopoietic transplantation on clonal expansion, suggesting different stressors can promote expansion of distinct long-lived clones.